Studies on DNA Molecules in Identification of Unclaimed or Missing Dead Bodies Presumed Death in Western Kenya Utilizing Physical Comparison Standards - Maurice B. Silali; W. Odero; E. Rogena (Highlights on Medicine and Medical Science Vol. 1, 2021)
Medico-legal form bench-mark of health determinants and provide integrated services towards criminal justice support in health. Investigations of medico-legal approaches are multifaceted and require expertise of multidisciplinary teams of skilled practitioners from various fields. Globally, over 44 million cases of unclaimed bodies or missing dead persons (UCBOMDPs) occur annually, 88% of these cases are in Sub Saharan Africa. In Kenya and western Kenya, rate of UCBOMDPs from road traffic accidents accounts 30% and 10% respectively, 80% of these UCBOMDPs are associated with limited access to affordable quality comparison tests for identifications, attributed to the increased prevalence of health and occupational hazards in population health. The current investigations aimed at identifying UCBOMDPs from public mortuaries, by quantifying demographic data and determining DNA finger print and chemical tests (electrophoresis) using comparison standards. In Exploratory and cross sectional, 235 respondents were investigated through purposive and saturated sampling using Finger print forms, structured questionnaires, focus group discussions (FGDs), observations and key informant interviews (KII) guides to collect data. Analyzed statistical inferences and contents analysis to saturation, results showed, 94% of mortuary service providers in tier 4 were primary and secondary education drop outs of males, on contract jobs with limited access to quality services in mortuary science, contrarily to females and males counterparts from tiers 5 and 6 mortuary facilities on permanent and trained. Rate of gross infection in public mortuaries and congestion had significant, OD, (2.2, 0.44). Prevalence of male being admitted as UCBOMDPs was significant due to being family bread winners, OD (8.3, 0.12), RR (0.33), 95% CI (1.23, 1.02), significance were associated with male deliberately leaving IDs in houses due to identity. Utilization of Dactylography was significant, than electrophoresis method, P value (0.67), OD (4.8, 1.3) due to high costs, procedures, DNA quantifying reagents and next of kin sampling for comparisons. Need for quality service advocacy in Department of Forensic Pathology to develop subsidized functional DNA chemical structures